Empirical linkages between ICT, tourism, and trade towards sustainable environment: evidence from BRICS countries. Issue 2 (10th July 2023) - Zafar, Syed Zeeshan; Zhilin, Qiao; Mabrouk, Fatma; Ramirez-Asis, Edwin; Alzoubi, Haitham M.; Hishan, Sanil S.; Michel, Mivumbi
Abstract: There is a growing utilisation of information and communication technologies (ICT) in the recent digital era. Trade and tourism have also attained attention as determinants of environmental sustainability. Therefore, this study investigates linkages between ICT, tourism, trade, economic growth, and environmental sustainability in BRICS economies. Advanced panel estimation entitled cross-sectionally augmented autoregressive distributed lags (CS-ARDL) was applied from 1990 to 2019. Findings suggest the adverse effect of tourism, trade, and growth factors on environmental sustainability, whereas ICT helps promote a sustainable environment among the targeted economies. Likewise, the short-run results prove that economic growth and tourism are prone to ecological health, while trade possesses an insignificant influence on ecological sustainability. These results suggest the integration of ICT in trade and tourism sectors to mitigate their negative ecological consequences.